PART II. EVALUATION OF 40AR-39AR QUARTZ AGES: IMPLICATIONS FOR FLUID INCLUSION RETENTIVITY AND DETERMINATION OF INITIAL 40AR/36AR VALUES IN PROTEROZOIC SAMPLES - Kendrick M.A.; Miller J.M.; Phillips D. (My University, 2006)
The argon isotope systematics of vein-quartz samples with two different K-reservoirs have been evaluated in detail. Potassium is hosted by ultra-high-salinity fluid inclusions in quartz samples from the Eloise and Osborne iron-oxide-copper-gold (IOCG) deposits of the Mt Isa Inlier, Australia. In contrast, K is hosted by accidentally trapped mica within lower-salinity fluid inclusions of a sample selected from the Railway Fault, 13 km south of the Mt Isa copper mine, Australia. Imprecise apparent ages have been obtained for all of the samples studied and conclusively demonstrate that quartz fluid inclusions are retentive to Ar and have not leaked over billions of years. IOCG samples that host K in fluid inclusions only, have K/Cl values of <1 and the ages obtained represent the maximum ages for mineralization. In contrast, the Railway Fault samples that include accidentally trapped mica have K/Cl values of ?1. Excess 40ArE plus Cl hosted by fluid inclusions, and radiogenic 40ArR plus K, are strongly correlated in these samples and define a plane in 3D 40Ar-36Ar-K-Cl space. In this case, the plane yields an ’excess 40ArE’ corrected age of ?1030 Ma that is 100’s of Ma younger than nearby Cu-mineralization at Mt Isa. The age is interpreted to reflect 40Ar-loss from the accidentally trapped mica into the surrounding fluid inclusions, and is not related to the samples’ age of formation. The initial 40Ar/36Ar value of fluid inclusions is widely used to provide information on fluid origin. For the IOCG samples that host K in fluid inclusions only, the initial 40Ar/36Ar values are close to the measured values at every temperature of stepped heating experiments. For samples that include accidentally trapped mica, the correction for post-entrapment radiogenic 40ArR production is significant. Furthermore, because 39ArK present in accidentally trapped mica crystals is released at different temperatures to radiogenic 40ArR lost to the surrounding fluid inclusions, intra-sample 40Ar/36Ar variation cannot be reliably documented. The results demonstrate that noble gas analysis is readily applicable to Proterozoic, or older, samples but that if K-mineral impurities are present within quartz the abundance of K must be determined before calculation of mean 40Ar/36Ar values that are representative of the samples’ initial composition. ? 2006 Elsevier Inc. All rights reserved.
Keywords: ARGON ISOTOPE; FLUID INCLUSION; POTASSIUM-ARGON DATING; PROTEROZOIC; QUARTZ VEIN; Докембрий::Протерозой; Precambrian::Proterozoic